Globalisation and labour market in China - Feicheng, Wang (2017)
This thesis empirically investigates the relationship between globalisation and labour market outcomes by exploring Chinese data. It is motivated by the fact that China has experienced a rapid pace of globalisation in the past two decades and has witnessed increasing wage inequality at the same time. It is a collection of three self-contained studies that examine the effects of various aspects of globalisation on employment or wage inequality.